The Theory of Degeneration and Morbid Inheritance in Medical Studies on Female Prostitution in Chile: 1920-1940 [la Teoría de la Degeneración y la Herencia Mórbida en Los Estudios Médicos Sobre la Prostitución Femenina en Chile: 1920-1940] - Goicovic-Donoso, I; Gálvez-Comandini, A (Universidade Federal do Rio Grande do Sul, 2022)
This article analyzes how the scientific idea of degeneration in prostitutes served to reaffirm their human inferiority, and their potential social danger, associated with deviant and immoral sexual behaviors, linked to the spread of venereal diseases. In Chile, between 1920 and 1940, much of the medical and health knowledge about prostitution was built on the basis of mental inferiority in prostitutes and their consequent moral degradation, as an expression of a morbid inheritance enhanced by a hostile social environment. The influence of degeneration theory, supported by eugenics and positivist criminology, contributed to a stigmatized stereotype of the prostitute as the epitome of female abnormality deviant sexuality and corrupt morality in women. In order to this, we have reviewed some of the main medical works produced in Chile between 1920 and 1940, that address exclusively prostitution, which reveal the characteristics and paradigms that permeated medical production in this regard. © 2022 Universidade Federal do Rio Grande do Sul. All rights reserved.